Glaucoma. Issue 6 (June 2017) - Davis, Abigail; Gilhooley, Michael James
The term, glaucoma, describes a group of conditions that are characterised by progressive optic nerve damage. Untreated glaucoma causes progressive visual field loss and eventually blindness. There are four main types: primary open angle glaucoma, acute angle closure glaucoma, secondary glaucoma, and congenital glaucoma. Primary open angle glaucoma is a common condition; it affects 2.1% of the UK population and is the second-most-common cause of blindness in the UK. Incidence and prevalence increase with age. Intraocular pressure is the only modifiable risk factor for progression of glaucoma; treatment to reduce intraocular pressure can prevent progression of optic nerve damage and preserve vision. Acute angle closure glaucoma is an ophthalmic emergency and prompt recognition and treatment of the condition is sight-saving. This article will discuss the aetiology, diagnosis and management of primary open angle and acute angle closure glaucoma, the role of GPs in supporting patients with glaucoma, and summarise the Driver and Vehicle Licensing Agency guidance relevant to these patients.